Tantangan dan Strategi Pelestarian Tradisi Hindu Kaharingan Di Era Modernisasi - Rupiadi Rupiadi; I Gede Arya Juni Arta (Fakultas Dharma Duta dan Brahma Widya, 2025)
This study aims to comprehensively analyze the various challenges in preserving the Hindu Kaharingan tradition in Central Kalimantan amidst the rapid currents of globalization and modernization. Using a literature study method that examines previous research, the findings reveal that globalization has led to a decline in youth participation in ritual activities, a shift in spiritual values, and a transformation of local lifestyles toward more modern and pragmatic orientations. Nevertheless, the study specifically shows that the preservation of the Hindu Kaharingan tradition can still be sustained through the reinforcement of local wisdom values within formal and non-formal education systems, the optimization of the roles of traditional and religious leaders as cultural preservation agents, and the effective utilization of information technology and social media as tools for education and the dissemination of traditional values among the younger generation. Therefore, a collaborative and adaptive preservation strategy—through the synergy between local culture and technological advancement—has proven to be an effective approach to ensuring the continuity and relevance of the Hindu Kaharingan tradition in the modern era.